Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Gittman, Rachel K.; Baillie, Christopher J.; Arkema, Katie K.; Bennett, Richard O.; Benoit, Jeff; Blitch, Seth; Brun, Julien; Chatwin, Anthony; Colden, Allison; Dausman, Alyssa; DeAngelis, Bryan; Herold, Nathaniel; et al. (Frontiers in Marine Science, 2019)
Coastal ecosystems are under pressure from a vast array of anthropogenic stressors, including development and climate change, resulting in significant habitat losses globally. Conservation policies are often implemented with the intent of reducing habitat loss. However, losses already incurred will require restoration if ecosystem functions and services are to be recovered. The United States has a long history of wetland loss and recognizes that averting loss requires a multi-pronged approach including mitigation for regulated activities and non-mitigation (voluntary herein) restoration. The 1989 “No Net Loss” (NNL) policy stated the Federal government’s intent that losses of wetlands would be offset by at least as many gains of wetlands. However, coastal wetlands losses result from both regulated and non-regulated activities. We examined the effectiveness of Federally funded, voluntary restoration efforts in helping avert losses of coastal wetlands by assessing: (1) What are the current and past trends in coastal wetland change in the U.S.?; and (2) How much and where are voluntary restoration efforts occurring? First, we calculated palustrine and estuarine wetland change in U.S. coastal shoreline counties using data from NOAA’s Coastal Change Analysis Program, which integrates both types of potential losses and gains. We then synthesized available data on Federally funded, voluntary restoration of coastal wetlands. We found that from 1996 to 2010, the U.S. lost 139,552 acres (~565 km2) of estuarine wetlands (2.5% of 1996 area) and 336,922 acres (~1,363 km2) of palustrine wetlands (1.4%). From 2006 to 2015, restoration of 145,442 acres (~589 km2) of estuarine wetlands and 154,772 acres (~626 km2) of palustrine wetlands occurred. Further, wetland losses and restoration were not always geographically aligned, resulting in local and regional “winners” and “losers”. While these restoration efforts have been considerable, restoration and mitigation collectively have not been able to keep pace with wetland losses; thus, reversing this trend will likely require greater investment in coastal habitat conservation and restoration efforts. We further conclude that “area restored”, the most prevalent metric used to assess progress, is inadequate, as it does not necessarily equate to restoration of functions.